Answer:
all work is answer and shown and pictured
Answer: Use the PEMDAS rule
Step-by-step explanation: 0z+3z+5=2(z-3)=
z= -1
you need to do the z numbers all together and the normal numbers together then subtract them to get -1
I hope that I help you
Answer:
Step-by-step explanation:
U would add it even though it looks like u need to multiply but u don’t. In order to add, u need to find the lcd of them both which is 12. 10/12 + 9/12. 19/12 or 1 7/12.
Answer:
(2 × 7 × 13) / (7 × 11) =
((2 × 7 × 13) ÷ 7) / ((7 × 11) ÷ 7) =
(2 × 7 ÷ 7 × 13)/(7 ÷ 7 × 11) =
(2 × 1 × 13)/(1 × 11) =
(2 × 13)/11 =
26/11;
Step-by-step explanation:
Answer:
Step-by-step explanation:
Pyramid height should be 14
Base area should be 14*14(196)
So, Base area is 196
1. Multiply the Base area by the height of the pyramid:
196*14=2744
2. Divide the number above by 3:
2744/3=914.7